2023
DOI: 10.3390/s23104613
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic Radio Access Network Subslicing with User Clustering and Bandwidth Subpartitioning

Abstract: In 5G and beyond, the network slicing is a crucial feature that ensures the fulfillment of service requirements. Nevertheless, the impact of the number of slices and slice size on the radio access network (RAN) slice performance has not yet been studied. This research is needed to understand the effects of creating subslices on slice resources to serve slice users and how the performance of RAN slices is affected by the number and size of these subslices. A slice is divided into numbers of subslices of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…If poor-BLER UEs are in the slice, the slice utilization is high and goodput is low, then operation "merge" was decided. However, our other previous work has shown that smaller subslices performed better, if UE BLER was worse [6].…”
Section: Analyzementioning
confidence: 61%
See 1 more Smart Citation
“…If poor-BLER UEs are in the slice, the slice utilization is high and goodput is low, then operation "merge" was decided. However, our other previous work has shown that smaller subslices performed better, if UE BLER was worse [6].…”
Section: Analyzementioning
confidence: 61%
“…Thirdly, subslices with decision "split" are split: UEs are clustered into two and slice bandwidth is split into two, that is RBs are divided to UE groups proportional to group Algorithm 1 Execute function The base algorithm for splitting a subslice is taken from [6] and modified to fit to the UEs which request different rates. First, the minimum subslice size in RBs, S min is converted to minimum subslice sum rate using Algorithm 2 Split function…”
Section: E Executementioning
confidence: 99%